The Techniques For Teaching Vocabulary At SMP Muhammadiyah 10 Surakarta In 2016-2017 Academic Year - Wahyu Hidayat, Irfan; , Mauly Halwat Hikmat, Ph. D (2017)
ABSTRACT This study is aimed to describe the techniques used to develop students' vocabulary, explain the purpose of each technique used, and to identify the problems faced by teachers in the learning process to develop vocabulary. This study used qualitative descriptive approach. The subjects of this study are an English teacher and 8th grade students of SMP Muhammadiyah 10 Surakarta. Data were taken from interviews, observation, and documentation. The data of this study were field notes and interview transcript about teaching technique for vocabulary. Techniques for analyzing the data are data reduction, data display, and data verification. The findings of the research show that the techniques used by the teachers in developing the vocabulary at SMP Muhammadiyah Surakarta 10 are series of picture and animation video. The purposes of using those techniques are to make students understand the material and not get bored in following the teaching and learning activities, and students are enthusiastic and interested in learning vocabulary. The three problems faced by teachers, namely classroom management, teaching media, and vocabulary accomplishment. Keywords: Technique for teaching, vocabulary